Epstein-Barr Virus Nuclear Antigen 1 Recruits Cyclophilin A to Facilitate the Replication of Viral DNA Genome - Xin, Shuyu; Du, Shujuan; Liu, Lingzhi; Xie, Yan; Zuo, Lielian; Yang, Jing; Hu, Jingjin; Yue, Wenxing; Zhang, Jing; Cao, Pengfei; Zhu, Fanxiu; Lu, Jianhong (Frontiers in Microbiology, 2019)
Epstein-Barr virus (EBV) nuclear antigen 1 (EBNA1)-mediated DNA episomal genome replication and persistence are essential for the viral pathogenesis. Cyclophilin A (CYPA) is upregulated in EBV-associated nasopharyngeal carcinoma (NPC) with unknown roles. In the present approach, cytosolic CYPA was found to be bound with EBNA1 into the nucleus. The amino acid 376-459 of the EBNA1 domain was important for the binding. CYPA depletion attenuated and ectopic CYPA expression improved EBNA1 expression in EBV-positive cells. The loss of viral copy number was also accelerated by CYPA consumption in daughter cells during culture passages. Mechanistically, CYPA mediated the connection of EBNA1 with oriP (origin of EBV DNA replication) and subsequent oriP transcription, which is a key step for the initiation of EBV genome replication. Moreover, CYPA overexpression markedly antagonized the connection of EBNA1 to USP7, which is a strong host barrier with a role of inhibiting EBV genome replication. The PPIase activity of CYPA was required for the promotion of oriP transcription and antagonism with USP7. The results revealed a strategy that EBV recruited a host factor to counteract the host defense, thus facilitating its own latent genome replication. This study provides a new insight into EBV pathogenesis and potential virus-targeted therapeutics in EBV-associated NPC, in which CYPA is upregulated at all stages.